2021
DOI: 10.1039/d1fd00030f
|View full text |Cite
|
Sign up to set email alerts
|

Peptide lipidation in lysophospholipid micelles and lysophospholipid-enriched membranes

Abstract: Acyl transfer from lipids to membrane-associated peptides is a well-documented process, leading to the generation of a lipidated peptide and a lysolipid. In this article we demonstrate that acyl transfer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It has also been demonstrated that peptides are able to undergo similar processes with lysolipids. 280 A consequence of peptide lipidation in this manner is expected to be an increase in the membrane affinity of the lipidated peptide. This will be reflected by irreversible membrane binding.…”
Section: Intrinsic Lipidationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been demonstrated that peptides are able to undergo similar processes with lysolipids. 280 A consequence of peptide lipidation in this manner is expected to be an increase in the membrane affinity of the lipidated peptide. This will be reflected by irreversible membrane binding.…”
Section: Intrinsic Lipidationmentioning
confidence: 99%
“…Generally, both higher temperatures and increased salt concentrations favored the reaction, but the effects of other parameters were found to be small. It has also been demonstrated that peptides are able to undergo similar processes with lysolipids . A consequence of peptide lipidation in this manner is expected to be an increase in the membrane affinity of the lipidated peptide.…”
Section: Aminolysis and Transesterificationmentioning
confidence: 99%